2016
DOI: 10.1063/1.4942855
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in hexagonal and cubic polymorphs of BaTiO3

Abstract: BaTiO3 appears in cubic and hexagonal variants, both of which are centrosymmetric. Samples of cubic BaTiO3 are known to exhibit breaking of the centric symmetry locally and globally. It has been proposed that the local symmetry breaking originates in polar regions, the precursors of the ferroelectric phase. Origins of the macroscopic symmetry breaking, which are not well understood, have been previously tentatively correlated with inhomogeneities in the samples, such as strain gradients that may align or redis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Later, Yu et al synthesized h‐BaTiO 3 crystals using a pressurized electrostatic levitation furnace, which exhibited a giant dielectric constant ( ε ′ ~ 10 5 at 5 kHz) at room temperature, which may arise from the Maxwell‐Wagner effect contributed by the interfacial boundaries consisting of crystal defects 14,15 . Hashemizadeh et al reported that the permittivity of h‐BaTiO 3 ceramics may be affected by the concentration of defects 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Yu et al synthesized h‐BaTiO 3 crystals using a pressurized electrostatic levitation furnace, which exhibited a giant dielectric constant ( ε ′ ~ 10 5 at 5 kHz) at room temperature, which may arise from the Maxwell‐Wagner effect contributed by the interfacial boundaries consisting of crystal defects 14,15 . Hashemizadeh et al reported that the permittivity of h‐BaTiO 3 ceramics may be affected by the concentration of defects 16 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Hashemizadeh et al reported that the permittivity of h-BaTiO 3 ceramics may be affected by the concentration of defects. 16 SLS, as an additive manufacturing technique, offers freedom to design and produce complex geometric build-parts without the use of molds. 17,18 SLS fabricates dense parts by using a continuous-wave (CW) laser beam to sinter the material powders selectively and additively layer-by-layer to build 3D objects.…”
mentioning
confidence: 99%
“…The possible interpretation of the enhanced flexoelectricity in perovskites was initially accounted for the non-crystalline polar-phases or polar nano-regions existing in the perovskites [27][28][29][30]. Recently, Damjanovic et al contended that the origin of enhanced flexoelectricity was actually attributed to the inner micro strain generated from the material densification process, despite the on-going controversy [31,32]. This paper will study flexoelectricity in BST materials with various densifications, and hence explore the interplay of the material densification and the related flexoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric materials based on BaTiO3 undergo a phase transition from a non-centrosymmetric polar ferroelectric phase to a cubic paraelectric centrosymmetric phase at Curie temperature (Tc) where spontaneous polarization is lost. However, recently it has been shown that cubic BaTiO3 phase exhibits breaking of nominal centric symmetry and exhibits polarization which was explained with the presence of polar nano-regions [1].…”
mentioning
confidence: 99%